G352(P) Paediatric dental safer airway & sedation for non-anaesthetists (PD-SASNA) training – collaboration beyond the ward. (24th May 2017) - Moran, A; Keane, O; Loo, Y; Gleeson, C; Calvert, S
Abstract : Aims: The Intercollegiate Advisory Committee for Sedation in Dentistry (IACSD) published national standards for the provision of safe conscious sedation (CS) in dentistry in 2015. The purpose of developing this course was to improve patient safety, in the provision of paediatric CS training in our dental department, with particular attention to human factors training in medical emergencies. The departmentacts as a tertiary referral centre including the treatment of paediatric patients with complex medical needs. Methods: The PD-SASNAcourse includes in-situ skills workshops and high-fidelity simulation scenarios with debrief of technical (including safeguarding) and non-technical skills. The course was designed by a paediatric dentist, paediatric registrar and anaesthetic registrar to meet the needs both of the staff and patients. Delegates comprised a multi-disciplinary group of 21 Dentist and Dental Nurses. Course performance was evaluated using 5 point semantic confidence and satisfaction scales. Opinions were collected via open-ended responses. Results: Participants rated their satisfaction of course content and delivery as 'extremely satisfied'. Comments included 'very realistic' and 'enjoyed the opportunity to deal with emergency scenarios as a team in the clinical setting'. A number of latent errors were identified during the day such as the closest available telephone located in a room to which none of the team knew the code. Staff also identified opportunities for quality improvement projects such as bringing the emergency drug box in line with current guidelines and having laminated protocols located in each room to improve functioning under stress during medical emergencies. Conclusion: In situ training using high-fidelity simulation and debrief alongside focused skills stations improves confidence in provision of safe CS and management of paediatric medical emergencies in dentistry. This course demonstrates the benefits of paediatricians collaborating with other healthcare professionals for the safety of our patients. Our remit to improve the quality of care offered to our paediatric patients extends beyond our immediate working environment and paediatricians have insight and knowledge to offer when such courses are being developed.